ANALISIS PENGARUH PEMENUHAN STANDAR PROSES DAN SARANA PRASARANA TERHADAP MUTU PENDIDIKAN PADA MASA PANDEMI COVID-19 - Aris Nurbawani (LP2M IAIN Tulungagung, 2021)
In the National Education Standards (SNP), there are eight minimum standards to realize quality national education. Two of them are process standards and learning facilities and infrastructure standards. Environmental changes due to the COVID-19 pandemic certainly have an impact on changes in the fulfillment of process standards and standards for learning facilities and infrastructure. Online learning has become a necessity as a learning method in universities during the COVID-19 pandemic. These changes can ultimately have an impact on the quality of education. This study aims to determine the effect of process standards and standards of learning facilities and infrastructure on the quality of education during the COVID-19 pandemic. The data used is primary data obtained from a survey of FATIK IAIN Ponorogo students. The results showed that the standard of the process and the standard of learning facilities and infrastructure had a significant effect either partially or simultaneously. Process standards and standards of learning facilities and infrastructure simultaneously affect the quality of education by 33.6%.